Optimizing Lettuce Seedling Growth through different Growing Media and Nitrogen Fertilization Regime: Optimizing Lettuce Seedling Growth through different Growing Media and Nitrogen Fertilization Regime - Abdulrahman, Bassam Lawan; Mustapha, Aishat; Mustapha, Fadil (Journal of Agricultural Sciences (Belgrade), 2025)
Abstract: The growth and yield of lettuce (Lactuca sativa L.) seedlings are significantly influenced by the properties of the growing medium and starter nitrogen fertilization. This study evaluated the effects of three growing media; soil, coco peat, and hydroponics under different nitrogen fertilization regimes. A completely randomized design (CRD) with four replications and six treatments was employed, including full and half NPK solutions for hydroponics, soil and coco peat, both with and without NPK. Chlorophyll content, plant height, root count, days to emergence, and dry weight were measured. Laboratory analysis was carried out to determine the properties of the growing media as well as the content of nitrogen, phosphorus, and potassium in the plants. Results showed significant differences (p < 0.001) among treatments. Hydroponics supported earlier seedling emergence (2.25 days on average), higher chlorophyll content (0.632 at week 2), greater plant height (5.53 cm at week 3), and higher dry weight (1.31 g) compared to soil and coco peat. While nitrogen content was highest in soil with NPK (7.17%), hydroponics full and half solutions recorded the highest phosphorus content (7.69 gkg-1 and 7.67 gkg-1, respectively). Root counts showed no significant difference across treatments, but dry weight was significantly higher in hydroponics. Overall, hydroponics proved to be the most effective medium, with the half NPK solution being more economical due to reduced fertilizer usage while maintaining high performance.
Keywords: Keywords: Lettuce (Lactuca sativa L.), growing medium, hydroponics, coco peat, soil, nitrogen fertilization, seedling emergence, chlorophyll content, nutrient uptake.